Effect of epinephrine on the oxidative desaturation of fatty acids in the rat - Tacconi de Gómez Dumm, Irma Nelva (1976)
The effect of epinephrine on the oxidative desaturation of fatty acids by liver microsomal prepara- tions of rats has been studied. Administration of epi- nephrine (1 mg/kg body weight) produced a significant decrease in desaturation of ( 1-14C)linoleic acid to y- linolenic acid and of ( 1 -14C)cr-linolenic acid to octadeca- 6,9,12,15-tetraenoic acid 12 hr after the injection. Lower doses produced a lesser effect on the A6-desaturation activity. Epinephrine administration modified the V,,, of linoleic acid desaturation but not the K,. There was also a slight increase in palmityl desaturation activity. The ef- fect of epinephrine on A6-desaturation activity was postulated to be mediated through an enhancement of the intracellular cyclic AMP levels that lead to an increase of a glucose metabolite. This metabolite would inhibit A6-desaturation activity.